(untitled) (Revista Latino-Americana de Enfermagem, 2012)
AIM: to analyze whether the nursing process method is used at public and private centers in the health area Gipuzkoa (Basque Country) and, if yes, to analyze in the framework of which model and how it is used. METHOD: cross-sectional study, based on the analysis of the nursing records used at the 158 centers studied. RESULTS: the nursing process is applied at 98% of the centers. It is applied at all public and 18 out of 21 private centers. Virginia Henderson's model is the most used to apply it, and most centers use nursing diagnoses, the NIC-NOC terminology and standardized care plans. CONCLUSION: the use of the nursing process is widespread in Gipuzkoa, with greater use at public than at private centers.